2008
DOI: 10.1161/circresaha.107.161737
|View full text |Cite
|
Sign up to set email alerts
|

c-kit Is Required for Cardiomyocyte Terminal Differentiation

Abstract: Abstract-c-kit, the transmembrane tyrosine kinase receptor for stem cell factor, is required for melanocyte and mast cell development, hematopoiesis, and differentiation of spermatogonial stem cells. We show here that in the heart, c-kit is expressed not only by cardiac stem cells but also by cardiomyocytes, commencing immediately after birth and terminating a few days later, coincident with the onset of cardiomyocyte terminal differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
87
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 30 publications
5
87
2
2
Order By: Relevance
“…Bernex et al (22) and Wouters et al (23) knocked reporters into the c-kit locus, but did not examine cardiac expression, and the dominant nature of the c-kit locus complicates this strategy. A minimal c-kit promoter strategy yielded similar results with the concordance of CD117 and anti-GFP staining that declined after birth (24,25). We show that embryonic and postnatal c-kit ϩ cells are in a mixed developmental state within the developing heart (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Bernex et al (22) and Wouters et al (23) knocked reporters into the c-kit locus, but did not examine cardiac expression, and the dominant nature of the c-kit locus complicates this strategy. A minimal c-kit promoter strategy yielded similar results with the concordance of CD117 and anti-GFP staining that declined after birth (24,25). We show that embryonic and postnatal c-kit ϩ cells are in a mixed developmental state within the developing heart (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Recent work (25) demonstrated that pressure overload results in augmented expression of c-kit in cardiomyocytes. Such expression could ref lect cardiomyogenesis from c-kit ϩ CPc, or could be the result of c-kit reexpression in committed myocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a recent report showed activation of a c-kit reporter after myocardial cryoinjury in the neonate (18), it is difficult to reach a conclusion about some minor role of progenitor cells in neonatal heart regeneration without carefully designed fate mapping studies. Although c-kit is expressed in a subset of cardiac progenitor cells, it is known that c-kit is also expressed during cardiomyocyte dedifferentiation (19,20), and proliferation (21), which are known features of the neonatal cardiac regenerative response. Therefore, future studies using detailed analysis of the extent and mechanism of regeneration in the neonatal cryoinjury model are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…23 c-Kit is also transiently expressed in cardiomyocyte precursors during development and in a rare cell population in the normal adult heart. Li et al 24 demonstrated that in the heart, c-Kit is expressed not only by cardiac stem cells but also by cardiomyocytes. Expression is observed immediately after birth and terminates a few days later and, thus, coincides with the onset of cardiomyocyte terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%